Clinical pathology of parrots : auto tutorial programs - Gunnarsson, Marie (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2006)
At the Veterinary Medicine Programme there is very little time allotted paid to exotic pets, which include psittacine birds, compared to other kinds of animals. However parrots are quite often seen as patients in the animal clinics in Sweden currently. Many veterinarians have unfortunately not enough knowledge to take care of such patients in a proper manner.